2008
DOI: 10.1097/bsd.0b013e318057529b
|View full text |Cite
|
Sign up to set email alerts
|

Raster Stereography Versus Radiography in the Long-term Follow-up of Idiopathic Scoliosis

Abstract: Using the parameters of lateral vertebral deviation and vertebral rotation, raster stereography accurately reflects the radiographically measured progression of idiopathic scoliosis during the long-term follow-up, but these parameters are not directly comparable with the Cobb angle. In the follow-up of scoliosis patients, the authors would recommend a raster-stereographic examination every 3 to 6 months and a radiographic examination every 12 to 18 months only, provided that raster stereography does not show r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 17 publications
1
67
0
1
Order By: Relevance
“…This, it is worth repeating, is something that has already been demonstrated by a considerable body of published literature (e.g. 4,5). In short, our message was not that rasterstereography can serve as a substitute for radiographs, when making clinical diagnosis of vertebral rotation.…”
mentioning
confidence: 55%
“…This, it is worth repeating, is something that has already been demonstrated by a considerable body of published literature (e.g. 4,5). In short, our message was not that rasterstereography can serve as a substitute for radiographs, when making clinical diagnosis of vertebral rotation.…”
mentioning
confidence: 55%
“…Radiographic-based measurements represent in fact the gold standard for diagnosis and for precisely quantify the amount of VR in AIS patients [5]. Rasterstereographic measurements, however, because of their safety profile, may be effectively used for monitoring over time of clinical changes [25], thereby confirming the possibility of their use for AIS follow-ups [22]. Interestingly, two patients were excluded from the present analysis, because the low quality of X-ray images did not allow to estimate anatomical landmarks needed for VR assessment through Raimondi method.…”
Section: Discussionmentioning
confidence: 99%
“…Rasterstereography is a method for stereophotogrammetric surface measuring of the back, originally developed by Drerup and Hierholzer [19]. It has been demonstrated that rasterstereography produces reliable data in patients with conservatively and surgically treated AIS, up to a Cobb angle of 80° [20,21], so that some authors have proposed to space out radiographs with rasterstereography in AIS long-term follow-up [22]. Since the importance of VR evaluation in AIS assessment, however, whether rasterstereography could give an accurate estimation of VR when compared with radiographs is an issue that remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…There was a positive correlation between changes in vertebral axial rotation and changes in Cobb angle and they also noted that Cobb angles remain constant during longitudinal growth, while stereography measurements are able to track this growth. More recently, Schulte et al 20 investigated the reliability and accuracy of raster stereography compared to X-rays in a longitudinal study in idiopathic scoliosis ( Figure 2). They analysed 16 patients with an average followup of 8 years (range of 3-10 years).…”
Section: Discussionmentioning
confidence: 99%